2014
DOI: 10.1177/0734242x14555804
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate induced respiration on the stability of bottom ash in landfill cover environment

Abstract: The municipal solid waste incineration bottom ash is being increasingly used to construct landfill covers in Sweden. In post-closure, owing to increased cover infiltration, the percolating water can add external organic matter to bottom ash. The addition and subsequent degradation of this external organic matter can affect metal mobility through complexation and change in redox conditions. However, the impacts of such external organic matter addition on bottom ash stability have not been fully evaluated yet. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…This would lead to a reduction of pH and enhanced formation of secondary mineral phases and reduced leaching of metals. This conclusion about the effect of microbial respiration and the ROM on the weathered ash is line with Ilyas et al (2014), who showed that the addition of organic matter and increased respiration lead to increased leaching metals in landfill covers.…”
Section: Resultssupporting
confidence: 86%
“…This would lead to a reduction of pH and enhanced formation of secondary mineral phases and reduced leaching of metals. This conclusion about the effect of microbial respiration and the ROM on the weathered ash is line with Ilyas et al (2014), who showed that the addition of organic matter and increased respiration lead to increased leaching metals in landfill covers.…”
Section: Resultssupporting
confidence: 86%